The regulation of postprandial lipemia in man - Cohen, Jonathan (Division of Physiological Sciences, 2018)
The regulation of the serum triglyceride responses to fat ingestion have been examined in normolipidemic men. To evaluate the existing methods for comparing chylomicron-triglyceride clearance, the oral and intravenous fat tolerance tests and a steady state duodenal perfusion method were compared. Good correlations (r > 0.8) were found between each of these methods. Since the intravenous fat tolerance test is independent of fat absorption, these data suggested that the serum triglyceride response to fat feeding was largely determined by the rate of chylomicron-triglyceride clearance. To determine the influence of the quantity and type of meal fat on postprandial serum triglyceride concentrations, the serum triglyceride responses to three different doses of dairy cream, and to standard doses of olive and sunflower oil were examined. For a given type of fat, the magnitude of postprandial lipemia (the integrated serum triglyceride excursion) varied directly with the quantity of fat in the meal. This finding suggested that the chylomicron- triglyceride clearance system(s) did not become saturated even after large fat meals. In addition, it appeared that the hormonal factors released in response to fat ingestion (some of which are known to increase lipoprotein lipase activity in vitro) did not increase the rate of chylomicron-triglyceride clearance. If the quantity of fat in a meal was fixed, then postprandial lipemia increased with increasing saturation of the triglyceride fatty acids. These differences did not appear to reflect differences in triglyceride absorption. Since acute fat feeding per se did not appear to stimulate chylomicron-triglyceride clearance, the effects of dietary proteins and carbohydrates were studied. The addition of up to 35g protein to a standard test meal did not affect postprandial lipemia. These results were supported by the observation that protein ingestion did not affect intravenous fat tolerance. Postprandial serum triglyceride concentrations were significantly influenced by carbohydrate ingestion. Fructose (50g) and sucrose (100g) markedly increased postprandial lipemia, although glucose ingestion did not. In agreement with earlier studies, glucose ingestion decreased serum triglyceride concentrations 2 hours after the meal. This effect was abolished by intraduodenal fat administration and by substituting starch for glucose in the test meal. The effects of glucose could be reproduced by iso-osmotic quantities of urea, however. These findings suggested that glucose ingestion did not increase chylomicron -triglyceride clearance. It is more likely that glucose delayed the absorption of triglycerides by slowing gastric emptying, and that this effect was partly related to the increased osmolarity of glucose- containing meals. The effects of chronic exercise on postprandial lipemia and chylomicron-triglyceride clearance were determined in endurance- adapted athletes. The serum triglyceride responses to large and small fat meals were lower in athletes than in sedentary men with comparable fasting triglyceride concentrations. These differences were not eliminated by a single bout of acute exercise in the sedentary men. The clearance of intravenously administered lntralipid, and chylomicron -triglyceride clearance assessed from steady state chylomicron-triglyceride concentrations during duodenal fat perfusion were faster in athletes than in the sedentary men. These data suggested that the low postprandial lipemia in athletes reflects increased chylomicron-triglyceride clearance caused by increased activity of the triglyceride clearing system(s). Given these considerations. it appears that the pathway(s) for chylomicron triglyceride clearance are extremely efficient in normal men and that these pathways are not subject to acute physiological regulation.